THE EVERYDAY AND THE ORDINARY IN A COUPLE OF SHORT STORIES BY DANIEL ODIJA (Филолошке студије, 2024)
The paper analyzes several of Daniel Odija’s short stories – mainly “Lica” (Faces), “Triptih” (Tryptich) and “Vistinska prikazna” (True Story), translated from Polish to Macedonian by Filip Dimevski (Goten, [2005] 2018). The main subject of interest and interpretation is the everyday and the ordinary and how these are artistically transformed into something uncommon, sometimes uncanny and/or extraordinary. Odija uses humor to present seemingly difficult topics, such as death, illness or hopelessness, and by doing so, he (or rather his narrators), flip and twist the expected, at the same time giving a comic note to what would otherwise be considered serious or grim. His style of presenting his characters and the various life events they go through is humoristic and whimsical, which almost erases the serious tone in certain situations, as well as the gravity of some conditions or life events (like the grandmother’s funeral in “Tryptich”). The main hypothesis is focused on exploring the way the everyday and the ordinary are transformed into something extraordinary and uncommon but not just for the sake of catching our – the readers – attention, but, rather, to artistically transform the mundane into something memorable. The descriptive method and the introspective method should lead us to the conclusion that Odija’s narrators transform everyday characters into artistic works of art through detailed, often comical, often bizarre, yet colorful descriptions and conspicuous presence, which turn them into something notable.